GIS based approach to understand the factors influencing the water level of the coastal aquifers in the ramnad district, Tamilnadu, India - N, Sivakarun; S, Chidambaram; C, Thivya; P, Paramaguru; K, Pradeep; N, Ganesh; P, Anandhan (International Journal of Advanced Geosciences, 2016)
An attempt has been made in this study to understand the factors influencing the variation in water level of the groundwater of the Ramnad district. The different factors considered for study were average water level, Land use pattern, tanks and rainfall pattern of the study area. The water level contours were spatially plotted for four months interval and their average was considered for comparison. The rainfall trend of the district was obtained by the Thiessen polygon method. Further the Average water level contour was overlaid over the land use, tanks and rainfall distribution maps to understand the spatial influencing factor and it was identified that the agricultural return flow and the tank intensity play a major role in the recharge of the groundwater of this coastal aquifers.